APE1 interacts with the nuclear exosome complex protein MTR4 and is involved in cisplatin‐ and 5‐fluorouracil‐induced RNA damage response. (15th November 2022) - Codrich, Marta; Degrassi, Monica; Malfatti, Matilde Clarissa; Antoniali, Giulia; Gorassini, Andrea; Ayyildiz, Dilara; De Marco, Rossella; Verardo, Giancarlo; Tell, Gianluca
Abstract : The nuclear RNA surveillance mechanism is essential for cancer cell survival and is ensured by the RNA nuclear exosome including some co‐factors, such as the RNA helicase MTR4. Recent studies suggest an involvement of DNA repair proteins such as apurinic/apyrimidinic (AP) endodeoxyribonuclease 1 (APE1), a major endodeoxyribonuclease of Base Excision Repair (BER), in RNA metabolism and RNA decay of oxidized and abasic RNA. Cisplatin (CDDP) and 5‐fluorouracil (5‐FU) are commonly used for the treatment of solid tumours. Whether APE1 is involved in the elimination of CDDP‐ or 5‐FU‐damaged RNA is unknown, as is its possible interaction with the nuclear exosome complex. Here, by using different human cancer cell models, we demonstrated that: (a) APE1 is involved in the elimination of damaged‐RNA, upon CDDP‐ and 5‐FU‐treatments, in a MTR4‐independent manner; (b) the interaction between APE1 and MTR4 is stimulated by CDDP‐ and 5‐FU‐treatments through lysine residues in the APE1 N‐terminal region and is, in part, mediated by nucleic acids and (c) APE1‐ and MTR4‐depletion lead to the generation of R‐loop formation causing the activation of the DNA damage response (DDR) pathway through the ATM‐p53‐p21 axis. Our data demonstrate a role of MTR4 in DDR underpinning the function of APE1 in controlling the RNA quality upon genotoxic treatments with possible implications in chemoresistance. Abstract : The mechanistic basis of nuclear RNA surveillance, which is essential for cancer cell survival, is poorly understood. The nuclear exosome is known to play a pivotal role, and its interaction with different classes of RNA is facilitated by co‐factors including MTR4. Here, Gianluca Tell and co‐authors show that APE1, a DNA repair protein that is involved in RNA decay, plays an MTR4‐independent role in the elimination of damaged RNA in cisplatin‐ or 5‐fluorouracil‐ treated human cancer cells. Furthermore, they characterize the interaction between APE1 and MTR4 and show that depletion of these proteins leads to activation of the DNA damage response pathway.